2002
DOI: 10.1080/10473289.2002.10470820
|View full text |Cite
|
Sign up to set email alerts
|

Development of Emission Factors for Polycarbonate Processing

Abstract: Emission factors for selected volatile organic compounds (VOCs) and particulate emissions were developed while processing eight commercial grades of polycarbonate (PC) and one grade of a PC/acrylonitrile-butadiene-styrene (ABS) blend. A small commercial-type extruder was used, and the extrusion temperature was held constant at 304 degrees C. An emission factor was calculated for each substance measured and is reported as pounds released to the atmosphere/million pounds of polymer resin processed [ppm (wt/wt)].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It would be a daunting task to design and implement emission studies for all combinations of extrusion variables. 9 To strike a balance between the inapplicability of static tests and the complexity of measuring each process, the SPI and major polyamide producers initiated work to develop baseline emission factors for polyamide processing under conditions that would provide reasonable reference data for similar processing operations. The seven resin types were evaluated and included a polyamide 66 homopolymer, a low-caprolactam polyamide 6 homopolymer, a polyamide 66/6 copolymer, an ethylene propylene diene monomer (EPDM)-toughened polyamide 66, a toughened polyamide 6, a mixture of polyamide 66 and polyamide 66/6 flame retarded with melamine, and a polyamide 66/6 flame retarded with Dechlorane Plus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be a daunting task to design and implement emission studies for all combinations of extrusion variables. 9 To strike a balance between the inapplicability of static tests and the complexity of measuring each process, the SPI and major polyamide producers initiated work to develop baseline emission factors for polyamide processing under conditions that would provide reasonable reference data for similar processing operations. The seven resin types were evaluated and included a polyamide 66 homopolymer, a low-caprolactam polyamide 6 homopolymer, a polyamide 66/6 copolymer, an ethylene propylene diene monomer (EPDM)-toughened polyamide 66, a toughened polyamide 6, a mixture of polyamide 66 and polyamide 66/6 flame retarded with melamine, and a polyamide 66/6 flame retarded with Dechlorane Plus.…”
Section: Introductionmentioning
confidence: 99%
“…This data was presented at an Air & Waste Management Conference in New Orleans in December 1998. 9 Reprints are available from SPI.…”
mentioning
confidence: 99%
“…A study in 2008 found that a large, industrial sized, twin-screw extruder produced airborne particles when using nano-aluminum oxide additive and polymethyl methacrylate (PMMA) or ABS as feedstocks (Tsai et al, 2008). A study in 2002 looking at extrusion of polycarbonate (PC) and a PC/ABS blend from a large, industrial sized, singlescrew extruder found that, while overall emissions were low, the PC/ABS blend had the highest emissions of particulates and VOCs (Rhodes et al, 2002). A study in 2015 found that extrusion of ABS plastic solid waste using an industrial extruder released styrene, ethylbenzene, xylene, toluene, and i-propylbenzene (He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%